2014
DOI: 10.1177/0164027514527834
|View full text |Cite
|
Sign up to set email alerts
|

Adult Child Caregiver Health Trajectories and the Impact of Multiple Roles Over Time

Abstract: Guided by stress process and life course theory, the purpose of this study was to examine adult child caregivers' psychological and physical health trajectories and how their multiple family (caregiving, marital, and parenting) and nonfamily (employment) roles contributed to these health outcomes over time. Seven waves of data from the Health and Retirement Study were analyzed for 1,300 adult child caregivers using latent growth curve models. Adult child caregivers have distinct psychological and physical heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 39 publications
0
38
1
3
Order By: Relevance
“…Similar contradictions are evident in research focusing on filial caregiving. Although it appears that daughters are more likely to be caregivers and to be primary or sole caregivers than are sons (Neal, Ingersoll‐Dayton, & Starrels, ) and some studies report finding higher levels of perceived burden and depression among daughters (Amirkhanyan & Wolf, ; Merz, Schulze, & Schuengel, ), others report finding no impact of gender on adult child caregivers' psychological well‐being over time (Barnett, ). Finally, although limited, research addressing the impact of parent care on adult children's marital relationships suggests that extended care provision can adversely affect marital quality, particularly for daughters (Bookwala, ).…”
Section: Background In Theory and Researchmentioning
confidence: 99%
“…Similar contradictions are evident in research focusing on filial caregiving. Although it appears that daughters are more likely to be caregivers and to be primary or sole caregivers than are sons (Neal, Ingersoll‐Dayton, & Starrels, ) and some studies report finding higher levels of perceived burden and depression among daughters (Amirkhanyan & Wolf, ; Merz, Schulze, & Schuengel, ), others report finding no impact of gender on adult child caregivers' psychological well‐being over time (Barnett, ). Finally, although limited, research addressing the impact of parent care on adult children's marital relationships suggests that extended care provision can adversely affect marital quality, particularly for daughters (Bookwala, ).…”
Section: Background In Theory and Researchmentioning
confidence: 99%
“…These situational exigencies contribute to the shape of caregivers’ life-course and health trajectories (Pavalko and Woodbury, 2000; Lee and Gramotnev, 2007; Marks et al, 2008; Pavalko et al, 2008; Barnett, 2015; Carmichael and Ercolani, 2016). …”
Section: An Institutional and Life-course Approachmentioning
confidence: 99%
“…He proposes: ‘The basic idea is take the measurement of ecological properties and social processes as seriously as we have always taken individual-level differences’ (Sampson, 2010: 72). There are a few exemplary studies that look at the broader social welfare context (Eichler and Pfau-Effinger, 2009; Jang et al, 2012; Sole-Auro and Crimmins, 2014; Tokunaga et al, 2015) in addition to exemplars viewing care work as a life-course process (Pavalko and Woodbury, 2000; Marks et al, 2008; Barnett, 2015; De Oliveira et al, 2015; Carmichael and Ercolani, 2016; Glauber, forthcoming). However, emphasis on dynamic processes and dynamic institutional contexts could capture what is working and what is not.…”
Section: Implications For Policy-relevant Researchmentioning
confidence: 99%
“…A longitudinal study of spousal pairs in the USA reported individuals who transitioned into the role of primary caregiver experienced elevated depressive symptoms compared with those who did not become caregivers . Other longitudinal studies have shown that adult children who provided care to their parent experienced detriments to their psychological health, but employment and marital status can attenuate this relationship . How caregivers’ health changes after their patients begin formal LTC treatment is an important and growing area of investigation.…”
Section: Introductionmentioning
confidence: 99%
“…13 Other longitudinal studies have shown that adult children who provided care to their parent experienced detriments to their psychological health, 14 but employment and marital status can attenuate this relationship. 15 How caregivers' health changes after their patients begin formal LTC treatment is an important and growing area of investigation. A recent study in the USA showed that as patients with Alzheimer's disease became institutionalized, the patients' caregivers did not experience relief in symptoms of depression or anxiety and actually used more anxiolytics after the patient was institutionalized.…”
Section: Introductionmentioning
confidence: 99%